Tips for a Successful Global Health Sabbatical - Jason T. Blackard (Ubiquity Press, 2019)
There is a high demand for global health experiences among medical students. However, creating and engaging successful global health experiences for students is not without significant challenges for faculty. Lack of broad global health knowledge, first hand experiences in a variety of global health settings, and limited faculty engagement in global health activities at their home institutions may limit overall effectiveness. Thus, sabbaticals may provide unique opportunities for faculty reinvigoration and development of new teaching and/or research activities in global health. This viewpoint stems from my sabbatical experiences in South Africa and Botswana during the 2016-17 academic year and includes important tips for ensuring a successful global health sabbatical.